Impact of Consultative Selling Techniques on The Sales Cycle: A Predictive Analysis Using Linear Regression - Masud , Sheikh Muhammed; Swain, Sukanta Chandra; Samal, Jayalaxmi (International Journal of Basic and Applied Sciences, 2025)
This study explores the impact of Consultative Selling Techniques (CST) on the duration and effectiveness of the sales cycle within five Information Technology (IT) firms, referred to as IT Firm 1 through IT Firm 5. In the IT industry, where sales cycles are typically pro-longed due to complex client needs and high-value solutions, understanding the role of CST is critical. Consultative selling emphasizes per-sonalized engagement, needs assessment, and solution-oriented communication, which are hypothesized to enhance sales performance. Us-ing historical sales data from the selected firms, this research applies a Linear Regression model to predict how the use of CST correlates with key sales metrics, particularly sales cycle length and conversion rates. The analysis identifies statistically significant relationships, demonstrating that a higher application of CST is associated with shorter sales cycles and improved conversion efficiency. These findings suggest that adopting CST not only accelerates the sales process but also contributes to more successful deal closures. The study offers practical implications for sales managers and professionals aiming to refine their sales strategies in competitive IT markets. This research lays a foundation for further investigations using advanced predictive models and examining broader outcomes such as customer retention, long-term revenue growth, and client satisfaction linked to consultative sales practices.
Keywords: Consultative Selling Techniques (CST); Sales Cycle Prediction; Linear Regression Analysis; IT Industry Sales Strategies; Sales Performance Optimization.